P3. Multimodal effective connectivity analysis reveals seizure focus and propagation in musicogenic epilepsy. Issue 8 (August 2015) - Klamer, S.; Rona, S.; Elshahabi, A.; Lerche, H.; Braun, C.; Honegger, J.; Erb, M.; Focke, N.
<x xml:space="preserve">Abstract</x> Objective Dynamic causal modeling (DCM) is a method to non-invasively assess effective connectivity between brain regions. This is especially interesting in epilepsy where the identification of epileptic network dynamics is of great clinical interest. 'Musicogenic epilepsy' is a rare reflex epilepsy syndrome in which seizures can be specifically elicited by musical stimuli and thus represents a unique possibility to investigate complex human brain networks and test connectivity analysis tools. We investigated the temporal sequence of epileptic activity spread in a case of musicogenic epilepsy using DCM for fMRI, high-density (hd-) EEG and MEG and validated results with intracranial EEG recordings. Methods A patient with musicogenic seizures triggered by Rap music was examined using hd-EEG/fMRI and simultaneous 256-channel hd-EEG/MEG to characterize the epileptogenic focus and propagation effects using source analysis techniques and DCM. Results were validated with invasive EEG recordings. Results We recorded one seizure with hd-EEG/fMRI and four auras with hd-EEG/MEG. Consistent across all modalities, we observed activations in the right mesio-temporal region as well as bilateral mesial frontal regions (Fig. 1) at seizure onset. Effective connectivity analysis of fMRI and hd-EEG/MEG indicated that right mesio-temporal neuronal activity drives changes in the frontal areas consistently in all three modalities (Fig. 2), i.e. seizures seem to originate in the right mesio-temporal region and propagate to the frontal region. These results could be confirmed by invasive EEG recordings, which clearly identified the seizure onset zone in the right hippocampus with fast propagation of seizure activity to the mesial frontal lobes. Conclusions Using DCM for fMRI, hd-EEG and MEG we were able to correctly localize focus and propagation of epileptic activity and thereby characterize the underlying epileptic network in a patient with musicogenic epilepsy. The concordance between all three functional modalities validated by invasive monitoring is noteworthy, both for musicogenic seizures as well as for effective connectivity analysis in general.